CCND1 Amplification Profiling Identifies a Subtype of Melanoma Associated With Poor Survival and an Immunosuppressive Tumor Microenvironment - Liu, Jun; Lin, Jing; Wang, Xuefeng; Zheng, Xiaobin; Gao, Xuan; Huang, Yingying; Chen, Gang; Xiong, Jiani; Lan, Bin; Chen, Chuanben; Si, Lu; Chen, Yu (Frontiers in Immunology, 2022)
Background: Although melanoma is generally regarded as an immunogenic cancer that will respond to immune checkpoint inhibitors (ICIs), melanomas with CCND1 amplification respond poorly to these therapies. Methods: We used data from tumor samples taken from Chinese patients with melanoma analyzed at the Geneplus Institute (n=302), as well as data from The Cancer Genome Atlas (TCGA) (n=367) and the Memorial Sloan Kettering Cancer Center (MSKCC) database (n=350) to estimate the prevalence of CCND1 amplification in melanoma, interrogate the relationship between CCND1 amplification and survival in patients with melanoma, and explore the molecular mechanisms of CCND1 amplification. We also established a murine model of melanoma harboring CCND1 amplification and utilized RNA-seq to verify the findings from human tissue samples. Results: Data from all three sources revealed a low frequency of CCND1 amplification co-occurring with BRAF V600, NRAS, NF1, and KIT mutations. Data from TCGA did not show a statistically significant correlation between CCND1 amplification and prognosis, irrespective of ICI use. In contrast, the MSKCC cohort showed that CCND1 amplification was an unfavorable prognostic factor for patients with melanoma, especially for patients who received ICIs and had a high tumor mutation burden (TMB). The TCGA data showed that CCND1 amplification was associated with a higher proportion of immunosuppressive cells and a lower proportion of immune boosting cells. Mice models supported the association between a suppressive immune microenvironment and CCND1 amplification. Furthermore, a Gene Set Enrichment Analysis (GSEA) analysis of data from the TCGA database suggested that signaling pathways involved in oxidative phosphorylation, reactive oxygen species, adipogenesis, and fatty acid metabolism were differentially enriched in melanoma tumors with CCND1 amplification. Finally, we observed a notable reduction in levels of angiogenesis-related molecules in a high CCND1 amplification group from the TCGA database. Conclusions: Melanoma with CCND1 amplification is an independent genomic subtype associated with a poor prognosis, an immunosuppressive TME, activated oxidative and lipid metabolism, and down-regulated angiogenesis. Therefore, avoiding ICIs and antiangiogenic agents, while employing CDK4/6 inhibitors alone or in combination with ICIs, and targeting oxidative and lipid metabolism pathways, may be effective therapeutic strategies for melanoma patients harboring CCND1 amplification.